Characterization of Two Kinases Involved in Thiamine Pyrophosphate and Pyridoxal Phosphate Biosynthesis in Bacillus subtilis: 4-Amino-5-Hydroxymethyl-2-Methylpyrimidine Kinase and Pyridoxal Kinase - Park, Joo-Heon (American Society for Microbiology, 2004)
Two Bacillus subtilis genes encoding two proteins (currently annotated ThiD and YjbV) were overexpressed and characterized. YjbV has 4-amino-5-hydroxymethyl-2-methylpyrimidine and 4-amino-5-hydroxymethyl-2-methylpyrimidine pyrophosphate kinase activity and should be reannotated ThiD, and B. subtilis ThiD has pyridoxine, pyridoxal, and pyridoxamine kinase activity and should be reannotated PdxK.